ANALISIS PENGARUH KUALITAS PRODUK DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI ULANG YANG DIMEDIASI OLEH KEPUASAN KONSUMEN (Pada Konsumen Samsung Smartphone di Undip) - Hudzaifah, Hudzaifah; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2018)
In the current era of globalization Smartphone has become part of the primary needs of society. This matter causes a tight competition among the Smartphone manufacturers across the World, especially in Indonesia. Among those phenomenon, Samsung Smartphone preciselly had been decreased their market share in recent years. This research aims to determine the factors that affect costumer repurchase intention of Samsung Smartphone to win the market and increase market share of the company.In this research the technique used in data retrieval is non probabillity sampling with purposive sampling. Populations and samples in this research are Undip students who have made purchases of Samsung Smartphone products that are known or can be found directly by researchers. This research using 100 respondents which are the Student across all Faculty in Diponegoro University. The data were collected by using questionnaires. The analysis and interpretation technique that being used is Multiple Regression Analysis, according to the model developed in this research, and operated through SPSS program version 21.The result of the research indicate that Product Quality and Brand Trust have an Positive impact on Customer Satisfaction. Than Product Quality, Brand Trust and Customer Satisfaction have an Positive impact on Customer repurchase intention. Customer satisfaction was the highly influenced variable toward customer repurchase intention.